Search for supersymmetry in events with photons, bottom quarks, and missing transverse momentum in proton-proton collisions at a centre-of-mass energy of 7 TeV with the ATLAS detector - Aad, G. (2013)
The integrated and differential fiducial cross sections for the production of a W or Z boson in association with a high-energy photon are measured using pp collisions at ffiffi s p ¼ 7 TeV. The analyses use a data sample with an integrated luminosity of 4:6 fb 1 collected by the ATLAS detector during the 2011 LHC data-taking period. Events are selected using leptonic decays of the W and Z bosons [Wðe ; Þ and Zðeþe ; þ ; Þ] with the requirement of an associated isolated photon. The data are used to test the electroweak sector of the Standard Model and search for evidence for new phenomena. The measurements are used to probe the anomalous WW, ZZ, and Z triple-gauge-boson couplings and to search for the production of vector resonances decaying to Z and W. No deviations from Standard Model predictions are observed and limits are placed on anomalous triple-gauge-boson couplings and on the production of new vector meson resonances.